Rice Supply Chain Analysis: Challenges and Opportunities in Increasing Rice Competitiveness in Baturaja Bungin Village, East OKU Regency - Vivi Fera Nicha (Universitas Galuh, 2025)
The rice supply chain in Baturaja Bungin Village, OKU Timur Regency, demonstrated a long and inefficient distribution pattern, resulting in low profit margins for farmers. The large number of intermediaries in the distribution chain caused price disparities and weakened the farmers' bargaining position. This study aimed to analyze the structure of the rice supply chain and evaluate the challenges and opportunities to improve the competitiveness of rice through a SWOT analysis approach. The results indicated that the direct distribution channel from farmers to consumers was the most efficient, although geographically limited. The total IFAS and EFAS scores of 3.84 and 3.55 respectively confirmed the strategic position of the rice farming sector in this village to develop through vertical integration strategies and digitalization of distribution systems. The novelty of this study lay in the integration of SWOT analysis with a supply chain restructuring approach based on local institutions and digital technology. The findings of this research were expected to serve as a reference for local governments and agricultural stakeholders in designing sustainable distribution efficiency and competitiveness improvement policies. Keywords: efficiency, distribution, rice supply chain, SWOT